Behavioral determinants of proclaimed support for environment protection policies - Björn Kauder; Niklas Potrafke; Heinrich Ursprung (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Using a representative survey of German university students, we confirm that proclaimed support for environment protection policies depends on socio-cultural factors and political ideology. Unlike most related studies for other countries, we find that the environmental policy stance of German partisans does not follow the left-right cleavage. Only about 25% of the social-democratic partisans wholeheartedly support environment protection policies, whereas 50% of the green partisans, who, in Germany, also belong to the political left, do so; and when controlling for socio-cultural influences, social-democratic partisans become undistinguishable from Christian-conservative and market-oriented partisans. Focusing on behavioral influences, we find that some of the respondents' psychological traits are not filtered through their political ideology but directly influence their proclaimed attitudes towards environment protection policies. We identify as important behavioral determinants the locus of control and psycho-logical traits that capture the respondents' susceptibility to making use of expressive rhetoric.
Keywords: D72; P16; Q51; Q58; 330; Environment protection; political preferences; ideology; identity; expressive behavior.